Effect of Rice Husk Addition on The Density and Impact Strength of Epoxy-Matric Composite Materials as Candidates for Eco-Friendly Brake Pads - Deni Fajar, Fitriyana; Muhammad Bustanul, Aripin; Saeful, Dimyati; Rusiyanto, Rusiyanto; Rahmat Doni, Widodo; Aldias, Bahatmaka; Samsudin, Anis; Wirawan, Sumbodo; Da Silva Guterres, Natalino Fonseca (INTI International University, 2023)
Automotive industry growth leads to increased demand for friction materials for brake pads. Asbestos is frequently employed because of its robustness and cost-effectiveness. Nevertheless, asbestos is a known carcinogen and has the potential to induce lung cancer. Hence, it is imperative to do research to identify an alternative substance to replace asbestos in brake pads. This study aims to investigate the impact of incorporating rice husk into epoxy matrix composites on the density and impact strength of the resulting materials, which are being considered as potential environmentally sustainable brake pads. The hand layup method was employed in this study to fabricate composite specimens. In this study, rice husk was utilized as a reinforcing agent, comprising 50% of the weight fraction in a composite material with an epoxy matrix. The composite material was combined with epoxy resin and hardener and then dried. It was subsequently divided into sections following the dimensions specified by the American Society for Testing and Materials (ASTM) standard. The sections were then tested to determine their density, hardness, and impact resistance. The study findings indicate that the composite specimen including rice husk exhibits a greater density of 1.35 g/cm3 , in contrast to the epoxy specimen with a 1.21 g/cm3 density. The augmentation in density holds significant importance in terms of load-bearing capability and resistance against damage. Incorporating rice husk into the composite material enhances its mechanical characteristics by diminishing porosity and augmenting impact resistance. The composite density attained in this investigation is within the spectrum of densities reported in brake pads available in the market